Clinical Profiles, Laboratory, Radiological and Outcome of COVID-19 Elderly Patients in Waikabubak Regional General Hospital, West Sumba - Laurentia, Lisbeth Maria; Effendi, Rambu Farah (Institute of Topical Disease Universitas Airlangga, 2022)
Cases of COVID-19 in the elderly show varied clinical characteristics. Elderly patients tend to be easily infected with COVID-19 and experience more severe conditions. This study aims to analyze the correlation between clinical characteristics of elderly COVID-19 patients and severity of COVID-19 disease at Waikabubak Regional General Hospital. Retrospective study from the medical records of elderly patients with confirmed COVID-19 at Waikabubak Regional General Hospital in March 2020 – September 2021. Inclusion criteria were elderly patients with confirmed COVID-19 who underwent treatment in COVID isolation room and did rapid antigen examination. The data collected were demographics, clinical manifestations, laboratory, radiological features, comorbid, and outcomes. Data analysis using SPPS for Window 12.0 version. There were 33 patients with 18 men and 15 women. Patients aged 65-74 are the most infected with COVID-19 and experience more severe conditions. Patients with no previous vaccine history were associated with the severity of COVID-19. Elderly patients with obesity tend to experience severe COVID-19 symptoms. Elderly patients with multi-comorbidities tend to experience severe COVID-19 symptoms. Dominant clinical symptoms in elderly patients were cough (33%), shortness of breath (25%) and fever (21%). Hematologic parameters that correlated with severity were hemoglobin, platelets, NLR, ALC and RBG. The most common radiological findings were bilateral infiltrates (92%). Mortality rate of elderly COVID-19 patients treated at the Waikabubak Regional General Hospital still tends to be high (42%). Age, vaccine history, obesity, shortness of breath, multi-comorbidities, laboratory and radiology significantly influence the severity of COVID-19 infection in the elderly.